Analisis Rhodamin B Dalam Saos Pentol Tusuk di Wilayah Banjarmasin - Rahmadani Rahmadani; Seva Bela Nata Asi; Shofa Tsuraya Salsabila; Tegar Fernanda Alfi; Tri Dewi Jayanti; Yesika Yesika (An-Najat, 2023)
Food is one form of basic human needs. Food additives (BTP) can be found in food, one of which is food coloring. Food coloring is divided into two, namely natural and synthetic. However, there are still foods that use illegal BTP, such as food coloring derived from Rhodamin B. Rhodamin B is a dye that is usually used in the textile industry. If this substance is consumed it can cause poisoning, impaired liver function to cancer. to find out the presence of Rhodamin B in the sauce of pentol skewers in Banjarmasin.This study uses qualitative analysis methods and quantitative analysis. Results were obtained for 4 samples obtained from 4 pentol skewer traders in Banjarmasin with S1 values of 5.01 mg/ml, S2 of 3.48 mg/ml, S3 of 3.53 mg/ml, S4 of 3.68 mg/ml ml. The concentration value indicates the presence and amount of Rhodamin B present in the sample The sauce used by pentol skewer traders in Banjarmasin contains Rhodamin B